The impact of Communicative Language Teaching Approach on Students’ Speaking Ability - Faridha, Noor (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
EFL Speaking is seen as a difficult skill that must be learned by most Indonesian students, especially those taking non-English programs. But teachers still have trouble coming up with the best way for their EFL speaking students to learn. So, this study suggests using Communicative Language Teaching (CLT) to help EFL students get better at speaking. CLT strategies focus on communication skills in the context of social situations. This makes it easy for students to learn how to speak English as a foreign language. This research aims to find out how the use of the Communicative Language Teaching (CLT) approach affects students' speaking skills. The research method used is a type of quasi-experimental research in which one group carries out tests before and after the research. Because there is no control group variable or only one group is the subject of the research. The pre-test is used to see how well students can do the task and the post-test is used to see whether there are changes in students' speaking abilities before and after treatment. This study found that using learning with CLT to teach English as a foreign language (EFL) speech in a college setting is helpful.